Søren Kierkegaards gennemslag i den eksistentielle og humanistiske psykologi, psykoterapi og psykiatri - Sørensen, Anders Dræby (Slagmark - Tidsskrift for idéhistorie, 2018)
Kierkegaard has long been known as a philosopher and theologican, but his writings have also made an important impact on the fields of psychology, psychiatry and psychotherapy. The article explores the reception of Kierkegaard’s thoughts in the humanistic and existential approaches to the psysciences. Kierkegaard has been most used by Ludwig Binswanger, Carl Rogers, Rollo May and Emmy van Deurzen for whom The Concept of Anxiety and The Sickness unto Death have been the two most influential texts.